La mente tra natura e tecnica - La Rocca, Claudio (Bollettino Filosofico, 2023)
In the first section, the article attempts to reconfigure the relationship between mind and technology beyond the classical schema according to which technology is a product of mind. Relying on Richard Gregory’s idea of Potential Intelligence and its developments in the theory of the extended mind, it is argued that the relationship between mind and technology is constitutive and original, so that in some sense mind is a technological product. The second section outlines – with reference to Mark Rowlands – a reading of the extended mind that does not identify it with the mere “extension” of its cognitive states to specific elements of the external world, but with the constitutive character of processes of instrumental relation to the world that could be linked to those theorised by Heidegger: disclosing and revealing activities that constitute at the same time the origin of significance. The third section emphasises the weight of technology in ‘shaping’ the mind and redefining our purposes, considering the idea of several authors (from Cassirer to Gehlen, from Ellul to Mumford) of a sort of “autonomy” of technology. Keywords: Extended Mind, Mind, Potential Intelligence, Significance, Technology